(untitled) (Journal of Engineering, 2014)
Numerical study of separation control on symmetrical airfoil, four digits (NACA 0012) by using rotating cylinder with double steps on its upper surface based on the computation of Reynolds-average Navier- Stokes equations was carried out to find the optimum configuration of unconventional airfoil for best aerodynamics performance. A model based on collocated Finite Volume Method was developed to solve the governing equations on a body-fitted coordinate system. A revised (k-w) model was proposed as a known turbulence model. This model was adapted to simulate the control effects of rotating cylinder. Numerical solutions were performed for flow around unconventional airfoil with cylinder to main stream velocities ratio in the range of 1 to 4 and for various positions of the steps on the airfoil from the leading edge, 0.1c, 0.2c, 0.3c, 0.4c, 0.5c for the first step and 0.5c, 0.6c, 0.7c, 0.8c for the second step with constant step depth and length of 0.03c and 0.125c respectively. Reynolds number of 700,000 which was based on the cord length (c), with angle of attacks 0, 5, 8, 10, 12, 15 degrees was considered for the assessment of the unconventional airfoil performance. The numerical investigation showed that the optimum configuration for the unconventional airfoil was found to be at velocities ratio (U/U∞=4) with the steps positions at 0.5c and 0.8c for best airfoil performance.